(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2020)
Individuals suffering from depression often experience a condition of isolation, which relegates them in a separate and neglected world of their own. In light of this issue, could audiovisual media contribute to drawing attention to the world of depression, and make it more familiar to the general population? The first part of this paper provides an extensive and in-depth description of depression. More specifically, by combining the psychiatric account of Thomas Fuchs with Jakob von Uexküll’s notion of Umwelt, it frames it in terms of a ‘psychopathology of time’, and introduces the notion of a self-enclosed ‘temporal world’ that is usually home (or rather cage) to depressed people. In turn, the second part of this paper discusses some media strategies that may actually disclose the temporal world of depression. After taking into account a cinematographic option and showing how it succeeds in making this world visible, it further examines a VR-based alternative in order to assess whether it can make the same world not simply visible, but fully accessible: that is, affording an up-close, first-person grasp of depression to ordinary, non-affected spectators.